2006
DOI: 10.1111/j.1463-1318.2006.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Sphincter‐preserving radiation therapy for rectal cancer: a simulation study using three‐dimensional computerized technology

Abstract: During a course of radiotherapy for most low- or mid-rectal cancers, the anal canal is included within the field of irradiation with a mean dose distribution to the sphincter of 33 Gy. Evaluation of 3DXRT with full sphincter block (mid-rectum) and partial sphincter block (distal rectum) is a feasible strategy to decrease the volume of anal sphincter carried to full dose without reduction in dose to the GTV. This approach, by minimizing treatment-induced damage to the anal sphincter, might improve functional ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrast to conventional protocols, IMRT conforms radiation tightly to tumors and high-risk regions, sparing nearby critical normal tissues. This technique is feasible for rectal carcinomas [ 29 ] and has been applied to SCCA in two studies, which similarly demonstrated that IMRT was effective (92% response rate), with a reduction of dermatologic toxicity and a better therapeutic index in comparison with historical standards [ 30 , 31 ].…”
Section: Novel Chemoradiation Protocolsmentioning
confidence: 97%
“…In contrast to conventional protocols, IMRT conforms radiation tightly to tumors and high-risk regions, sparing nearby critical normal tissues. This technique is feasible for rectal carcinomas [ 29 ] and has been applied to SCCA in two studies, which similarly demonstrated that IMRT was effective (92% response rate), with a reduction of dermatologic toxicity and a better therapeutic index in comparison with historical standards [ 30 , 31 ].…”
Section: Novel Chemoradiation Protocolsmentioning
confidence: 97%
“…It can reduce the received dose from original 33 Gy to 6 Gy 27 . For a certain portion of irradiation fields which include the anal sphincter and distal rectum, the dose should also be limited to 40~45 Gy 28 .…”
Section: Preoperative Radiotherapymentioning
confidence: 99%
“…In addition, a decrease in the volume of normal tissues in the radiation fields was also seen. Attempts are being made to selectively subtract the anal sphincter from the high-dose field in order to improve functioning outcome in patients with mid-rectal tumors scheduled for a low anterior resection [33] . Only lately, the IMRT technique with a five-field customized segmented plan has significantly reduced the volume of small and large bowel irradiated to high dose, which could potentially lead to less bowel toxicity [34] .…”
Section: Improvements In Radiotherapymentioning
confidence: 99%